Characteristics of nasal mucosal barrier in lambs at different developmental stages. (February 2023) - Zheng, Jian; Lin, Jian; Yang, Chengjie; Ma, Yichao; Liu, Peng; Li, Yucheng; Yang, Qian
Abstract: The mucosal barriers of a lamb's nasal cavity are composed of a multi-layer barrier designed to protect against the invasion of harmful microorganisms. However, despite the protective measures, respiratory pathogens still infect the sheep from the nasal cavity. Therefore, our study aimed to investigate the characteristics of lamb's nasal cavity barrier at different developmental stages. For nasal histological characteristics, our study revealed that the conchoidal curvature of the inferior nasal conch and the number of glands significantly increased with lamb development. For nasal mucosal barrier characteristics, physical and immune barriers were carefully explored. Initially, we observed that the thickness and proliferative capacity of nasal epithelial significantly increased from fetal to 21 days, which then decreased at 60 days. Then, our study showed that the number of goblet cells (GCs) of 21 days old lamb was significantly higher than in other stages of development. Besides, we found that the number of nasal immune cells, such as dendritic cells, CD3 + T cells, IgA + B cells, and nasal-associated lymphoid tissue (NALT), were all significantly increased not only from the proximal to distal side in the nasal cavity but also with their age. Totally, our study revealed various characteristics of the mucosal barriers of a lamb's nasal cavity, which provide a reference for explaining the susceptibility of respiratory tract infection in lambs. Highlights: The number of lamb's nasal immunocyte increased significantly from proximal to distal side, besides raised with age. The thickness, proliferative capacity and the number of goblet cells in the 21d lamb's nasal epithelium were highest. The feature analysis of lamb's nasal cavity is helpful to prevention and treatment of lamb's respiratory tract infection.